Measuring distributional effects of fiscal reforms - Andreas Peichl; Richard Ochmann (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2006)
The purpose of this paper is to provide an overview of how to analyse the distributional effects of fiscal reforms. Thereby, distributional effects shall be differentiated by four subconcepts, i.e. 1.) the traditional concept of inequality, 2.) the rather novel concept of polarisation, 3.) the concept of progression in taxation, and 4.) the concepts of income poverty and richness. The concept of inequality and the concept of income poverty are the by far most widely applied concepts in empirical analyses, probably since they appear to be the most transparent ones in their structure as well as the most controversial ones in political affairs. However, the concepts of richness, polarisation and progression in taxation shall additionally be subject of this analysis, since they appear to be useful devices on the course of analysing cause and effect of the other two concepts.
Keywords: D3; H2; J22; 330; Inequality; polarisation; progression; poverty; richness